PUBLICATION PRODUCTIVITY OF MALAYSIAN RESEARCHERS IN THE FIELD OF COMPUTER SCIENCE AND INFORMATION TECHNOLOGY - Gu, Yinian; A.N., Zainab (Malaysian Journal of Library and Information Science, 2001)
Searches made in the CD-ROM databases, COMPENDEX (1987-1999), IEL (IEE/IEEE Electronic Library) (1988-1999) and INSPEC (1990-1998) revealed a total of 389 publications contributed by Malaysian researchers in the field of computer science and information technology. The trend in output indicates rapid growth that is expected to continue in future. A total of 458 unique Malaysian authors contributed to the 389 publications. Collaboration between two authors was the dominant authorship pattern. Single-authored or more than 3-authored works were rare. The active authors were affiliated to a few institutions, with the Universiti Teknologi Malaysia, Universiti Sains Malaysia and Universiti Malaya accounting for the highest number of publications, either in the form of journal articles or papers in conference proceedings. The most active research areas include simulation system, control engineering, computer-assisted instruction, programming techniques, expert systems, asynchronous transfer mode, image processing, software engineering and digital signal processing and applications.